2020
DOI: 10.15361/1984-5529.2020v48n2p160-169
|View full text |Cite
|
Sign up to set email alerts
|

Fertilidade e carbono orgânico do solo em sistemas agroflorestais de duas décadas compostos de castanheira, cupuaçuzeiro e pupunheira na Amazônia Ocidental

Abstract: ResumoA Floresta Amazônica vem sendo substituída por diversos sistemas de uso, como pastagens e variados usos agrícolas. O objetivo deste estudo foi avaliar o efeito da implantação do sistema agroflorestal (SAF) na Amazônia sobre atributos químicos do solo em três SAFs, compostos por castanheira, cupuaçuzeiro e pupunheira, sendo o SAF A analisado aos 4 e 19 anos, o SAF B aos 7 e 22 anos, e o SAF C aos 6 e 21 anos após a implantação. Foram avaliados os teores de P, Ca 2+ , Mg 2+ , K + , H+Al, pH, SB, CTC, V% e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
2
0
6
Order By: Relevance
“…Therefore, eutrophic soil with a slight gradient in depth, which is desirable for the good development of both peach palm and Urochloa decumbens (Raij et al, 1997). The results are similar to the studies that observed an increase in the nutrients availability over time with the enrichment of the superficial layers of the soil due to the constant supply of organic matter (Butzke et al, 2020;Iwata et al, 2012;Montanari et al, 2016). Except for Mg/CEC, the other relationships showed variation between the evaluated systems.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, eutrophic soil with a slight gradient in depth, which is desirable for the good development of both peach palm and Urochloa decumbens (Raij et al, 1997). The results are similar to the studies that observed an increase in the nutrients availability over time with the enrichment of the superficial layers of the soil due to the constant supply of organic matter (Butzke et al, 2020;Iwata et al, 2012;Montanari et al, 2016). Except for Mg/CEC, the other relationships showed variation between the evaluated systems.…”
Section: Resultssupporting
confidence: 89%
“…In the fruit and seed production system, we observe that dynamics of mineral cycling and availability for the soil solution was not sufficient to maintain or improve the chemical conditions of the soil compared to pasture. We therefore recommended corrective practices in this management for soil enrichment, whether in chemical or organic form, as suggested by Butzke et al (2020) and Silva et al (2011). The peach palm heart palm management system showed high and medium P and Ca levels, respectively (Raij et al, 1997), that are justified by the use of maintenance fertilizers combined with greater nutrient cycling promoted by the cutting of the hearts of palm, since the biomass from the extraction was kept under the soil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A matéria orgânica fornecida pela serapilheira é a principal fonte de nutrientes para as plantas nas regiões tropicais (Caldeira et al, 2019;Moreira & Malavolta, 2004), havendo relação direta entre a diversidade de espécies de uma área, a qualidade da liteira e a disponibilidade de nutrientes (Machado et al, 2017). A decomposição da serapilheira pelos microorganismos do solo promove a ciclagem de nutrientes, melhorando a fertilidade do solo (Chaves et al, 2020), principalmente nas camadas superficiais, de 0 a 20 cm (Butzke et al, 2020). A remoção da serapilheira, por outro lado, pode prejudicar a atividade dos microorganismos do solo, com consequências negativas para a ciclagem de nutrientes (Maia et al, 2015;Reed et al, 2011).…”
Section: Matéria Orgânica E Carbono Orgânico Do Solounclassified
“…O maior constituinte da MOS é o carbono orgânico (CO), que desempenha um papel fundamental em quase todas as funções do solo (Signor et al, 2018). O aumento da biomassa de resíduos vegetais que formam a serapilheira é um dos principais responsáveis pelo acúmulo de carbono no solo, que se dá a partir da estabilização da MOS (Butzke et al, 2020). O estoque de C está relacionado, portanto, ao fornecimento contínuo e diversificado de matéria orgânica, responsável pela estrutura e desenvolvimento da comunidade microbiana no solo (Lammel et al, 2015).…”
Section: Matéria Orgânica E Carbono Orgânico Do Solounclassified